Children kneeling on the ground at San Jose State. - Gordon, John C. (photographer):::Creator::::::::::::
Children kneeling on the ground at San Jose State. Photograph shows seventeen boys in a circle kneeling on the floor with their heads on the ground. Some children have their hands on the back of their heads, on top of their heads or on the ground underneath their face.